The compensatory mechanism and clinical significance of hydrocephalus after cranioplasty - Qiu, Xiansheng; Wang, Dong; Chen, Li; Huang, Guanlin; Zhou, Xiaoping; Chen, Qiang; Wang, Zhanxiang (Frontiers in Neurology, 2023)
Objective Cranioplasty (CP) and ventriculoperitoneal shunt (VPS) are procedures required after decompression of the flap (DC) to protect the cranial frame and prevent hydrocephalus. This study evaluated the safety and efficacy of different surgical sequences of CP and VPS after DC and identified risk factors for necessary permanent VPS. Methods From January 2017 to December 2021, valid follow-up data were collected in 192 cases. The observation group preferred CP, and then evaluated whether to receive VPS according to the progress of hydrocephalus. the control group was prioritized for VPS and continued with CP after 1 week. The improvement of hydrocephalus symptoms, follow-up outcomes, and post-operative complications before and after surgery were compared between the two groups, and univariate analysis was used to determine the risk factors for necessary permanent risk factors for VPS. Results There were 86 cases (44.8%) in the observation group, who received CP first, while 106 cases (55.2%) in the control group received VPS and CP, respectively. There was no significant difference between the two groups according to Barthel index, FMAS, Mrs, GCS, and Evans index, and there was no statistical difference in complications between the two groups. However, in the observation group, hydrocephalus disappeared after CP operation in 29 cases (33.7%), and finally avoided VPS. Univariate analysis showed that the main etiology was related to the size of the skull defect, the distance of the talus margin relative to the flap to the midline, and lumbar puncture pressure was a predictor of the need for permanent VPS. Conclusion This study provides detailed information on the efficacy and complications of different sequences of preferential CP or VPS after DC surgery. We found that priority CP reduced the incidence of VPS surgery without affecting surgical outcomes and complications.